Smoke and ashes : a novel - Mukherjee, Abir (Mukherjee, Abir. Sam Wyndham, 2019)
Recognizing ritualistic injuries on a murder victim from a memory compromised by his opium addiction, Captain Sam Wyndham, aided by sidekick Surrender-Not Banerjee, struggles to solve two mysteries while hiding his personal demons from the Calcutta police force.